Remedial games - Tools for therapy - van Slagmaat, R.; Bas, M.; van Tuijl, A.; Schönsee, R. (International Journal of Computer Science in Sport, 2012)
Ranj Serious Games developed `Juf-in-a-Box`, an innovative system to train young children with fine motor skills disorder and method for preparatory writing based on gaming principles. Juf-in-a-Box is an educational, therapeutic computer game, developed in collaboration with experts in the field of pediatric physiotherapy, designed to offer a solution to fine motor skills disorder and writing problems within primary education.